SYTUACJA PRAWNA INWESTORÓW ZAGRANICZNYCH W POLSCE I NA BIAŁORUSI (porównanie Prawa działalności gospodarczej i Kodeksu inwestycyjnego Republiki Białoruś) - Struczewski, Jury (Wydział Prawa i Administracji UAM, 2002)
Liberalization of conducting business activity by foreign investors in both Poland and Belarus constitutes the most important element of the economic transformation in these two countries. On the basis of the analysis of the Polish Business Activity Act and the Investment Code of the Republic of Belarus one may notice considerable differences between the legal regulations, including the legal terminology. Therefore, for example, the activity of foreign investors in Poland is regulated by a parliamentary Act. However, such activity in Belarus is regulated by the Code. This Code is called the „Investment” Code and the term „foreign investors” is applied to foreign subjects conducting business activities in the Republic of Belarus. The Polish Business Activity Law Act differs from the Investment Code in the specification of the range of investment activity subjects. The Code stipulates that foreign states, their legal-administrative units and international organizations can also be considered to be foreign investors, while the Polish Act does not mention such subjects. Pursuant to the Act, business activity may be conducted in Poland by a partnership of foreign natural or legal persons that does not have the status of a legal person and has its main seat abroad. The Investment Code of the Republic of Belarus does not provide for the activity of a foreign organization without the status of a legal person in Belarus. Under the Act foreign entrepreneurs may set up branches and representative offices in the Republic of Poland. The issue of setting up branches and representative offices and conducting activity by the branches and representative offices on the territory of Belarus is not regulated in the Investment Code. The term „branch” does not exist in the Belarusian legislation. One of the basic principles of the Business Activity Law Act which regulates the conducting of business activities in Poland is the principle of reciprocity. The Investment Code does not include such a principle. The Business Activity Law Act maintains the principle of equal treatment of foreign and domestic subjects. The Investment Code of Belarus provides for the principle of national treatment of the foreign investors. However, one should mention at this point that the Investment Code has been in force only since 9 December 2001 and the legal situation of foreign investors is determined on the basis of the previous legal acts which have not been harmonized with this general principle of the Investment Code. Besides, Belarusian legal acts uphold many limits and exceptions concerning foreign investors. As a result, the legal system in force is not favourable enough to the influx o f foreign investments in Belarus.
LEGAL CONDITIONS FOR FOREIGN INVESTMENT IN POLAND AND BELARUS (comparison of the Polish Business Activity Law Act and the Investment Code of the Republic of Belarus)